Lipid Peroxidation Level on Moderate-Intensity Interval Exercise on Non-Athlete Adolescent - Sugiharto; Desiana Merawati; Olivia Andiana; Adi Pranoto (UNIB Press, 2022)
Exercise is commonly perceived as a pleasurable and healthy activity. However, it is classified as a complex activity that potentially enhances the formation of free radicals and oxidative stress. This study aims to analyze lipid peroxidation, as the biomarker of free radicals, in interval exercise. A total of 16 trained non-athlete male adolescents, aged 20-21 years old, with normal blood pressure, normal resting heart rate, and gave good level of physical fitness voluntarily participated in this study. The participants were randomly separated into two groups, namely the K1 (n=8, interval exercise with active resting medium intensity pedaling ergometer bike) and K2 (n=8, interval exercise with resting without pedaling the ergometer bike). The interval exercise was carried out at 60-70% HRmax intensity for 35 minutes. The blood sample for Malondialdehyde (MDA) level analysis, as the lipid peroxidation biomarker, was taken using Thiobarbituric acid reactive substances (TBARS). The blood samples were collected before and after the interval exercise. The obtained data were analyzed using the one-way ANOVA test with a 5% significance level. Our results suggest no significant different level of MDA, a lipid peroxidation biomarker, between the interval exercise with resting through medium intensity pedaling ergometer bike and the interval exercise with resting with no pedaling ergometer bike. However, the interval exercise resting through pedaling an ergometer bike presented relatively higher lipid peroxidation than the interval exercise resting without pedaling an ergometer bike. Therefore, following the free radical concept, interval exercise with resting through pedaling an ergometer bike is more beneficial than the exercise without pedaling an ergometer bike resting.